GeoGebraAs a Tool to Enhance Student Ability in Calculus - Arini, Florentina Yuni; Dewi, Nuriana Rachmani (KnE Social Sciences, 2019)
ThispaperdescribedtheuseofGeoGebrasoftwaretohelpstudentsinunderstanding Calculus material and its applications. GeoGebra is already used by more than 100 million students around the world. GeoGebra has the ability to minimize the difﬁculties of students who get Calculus subjects, especially students majoring in Natural Sciences and Engineering because this subject becomes a compulsory subject and a fundamental foundation in mathematics and its application across multidisciplinary ﬁelds such as medical, social sciences, psychology, and economics. Usually, the calculus course is given to ﬁrst-year university students as the foundation for next course requirement. However, the manual calculation in Calculus sometimes takes a long time as it requires mathematics skills to solve the problem. Therefore, the advantagesofusingGeoGebraare(a)helpingtoconveytheCalculusconceptmaterial to be more interesting, especially for the delivery of material concepts of functions, limits, derivatives, and integrals, (b) providing a more realistic image, especially for more complex calculus material, and (c) providing a faster and accurate solution. Keywords: GeoGebra, Natural Sciences, Engineering, Mathematics, Calculus